Impacts of Adjunct Incorporation on Flavor Stability Metrics at Early Stages of Beer Production. (2nd January 2023) - Maia, Carolina; Cunha, Solon; Debyser, Winok; Cook, David
Abstract: The fresh flavor of a beer brand is one of its most important quality parameters and should be retained as long as possible through shelf-life. Early stages of beer production can have significant impacts on beer flavor stability. The use of cereal adjuncts – either malted or unmalted – is now widespread practice in brewing. This laboratory mashing study investigated the impacts of incorporating common solid adjuncts (corn and rice) at increasing grist percentages (0-50%) on flavor stability indicators measured in wort. Sweet worts were analysed for metal ion levels (ICP-MS), thiol content (RP-HPLC), oxidative stability (EPR spectroscopy), staling aldehydes (HS-SPME-GC-MS), trihydroxy fatty acids (GC-FID), t -2-nonenal potential (GC-MS), color and thiobarbituric acid (TBI). Mashing conditions for each formulation were adjusted in order to achieve target FAN values. Unmalted rice or corn adjuncts significantly reduced the total metal ion content, color, TBI and staling aldehydes in sweet worts at 50% adjunct incorporation (p < 0.05), relative in each case to the respective all-malt control mash. Our findings showed that unmalted rice or corn adjunct incorporation generally improved flavor stability metrics in sweet worts when similar mashing conditions were applied, whilst increasing the length of the 'protein stand' in mashing to reach target FAN in general had a negative impact on flavor stability indicators – e.g., wort T150 values significantly decreased in each recipe at 25% and 35% adjunct relative to the 12.5% adjunct brew but increased again at 50% adjunct, presumably due to the prolonged proteolytic stand employed to achieve target FAN content.